Integrated Farming System: Key to sustainability in arid and semi-arid regions - RATHORE, V S; TANWAR, S P S; KUMAR, PRAVEEN-; YADAV, O P (The Indian Journal of Agricultural Sciences, 2019)
Ensuring higher productivity and profitability, gainful employment and adequate supply of food, feed, fodder and fiber for a growing human and livestock population, along with maintaining environmental sustainability are major challenges in agricultural production systems of arid and semi-arid regions. Integrated farming systems (IFS) comprising of many agri-innovations have the potential to meet such requirements. An association of individual and interdependent components of farming on a given piece of land, taking cognizance of available natural resources and the differential requirement of a wide range of farming community, remains the guiding principle of IFS. Research conducted across arid and semi-arid regions is reviewed here in order to understand the role of IFS in enhancing production, income and livelihood; minimizing risk associated with farming in arid and drier semi-arid regions; utilizing and conserving the resources; and in enhancing mitigation and adaptation to climate change. It has been conclusively established that IFS involving integration of different enterprises (crop, livestock, horticulture, forestry, poultry and fish) enhanced productivity, profitability, resource use efficiency, generated more employment and minimized resources degradation and risks. IFS, therefore, could be a key form of farming intensification needed for achieving future food security and environmental sustainability in arid and semi-arid regions. Promoting adoption of the location-specific IFS in future is linked directly with coherent policy, institutional commitment, infrastructure development, better coordination among different agricultural and rural development programme and agencies, and a stimulus package of incentives. The relevance of IFS in adaptation to and mitigation of climate change is also discussed.